2013
DOI: 10.1063/1.4819582
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis of thin film IPRTs in the range 100 °C to 600 °C

Abstract: Abstract. As opposed to SPRTs, the IPRTs succumb to hysteresis when submitted to change of temperature. This uncertainty component, although acknowledged as omnipresent at many other types of sensors (pressure, electrical, magnetic, humidity, etc.) has often been disregarded in their calibration certificates' uncertainty budgets in the past, its determination being costly, time-consuming and not appreciated by customers and manufacturers. In general, hysteresis is a phenomenon that results in a difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…This model was applied tothe raw experimental data and the results obtained are shown in Fig.4.The best fit line showed a correlation of R 2 = 0.9999999835 and returned (7). ρ(T)= -0.0000229505T 2 + 0.4876336188T + 135.1721950209 7Putting this in the correct format provides, ρ(T)= -0.000000581366T 2 + 0.003868504198T + 1.00000000000 (8) This shows that the required characteristic equation for Pt/Rh sensors was again returned and agrees well with the conclusions put forward by [13].In addition to the responses for Pt/Rh sensor obtained using (6) that exhibited resistivitytemperature profiles, the TCR valuealso coincides with experimental results. Therefore, the results obtained with the two-dimensional model are in conformity with experimental findings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model was applied tothe raw experimental data and the results obtained are shown in Fig.4.The best fit line showed a correlation of R 2 = 0.9999999835 and returned (7). ρ(T)= -0.0000229505T 2 + 0.4876336188T + 135.1721950209 7Putting this in the correct format provides, ρ(T)= -0.000000581366T 2 + 0.003868504198T + 1.00000000000 (8) This shows that the required characteristic equation for Pt/Rh sensors was again returned and agrees well with the conclusions put forward by [13].In addition to the responses for Pt/Rh sensor obtained using (6) that exhibited resistivitytemperature profiles, the TCR valuealso coincides with experimental results. Therefore, the results obtained with the two-dimensional model are in conformity with experimental findings.…”
Section: Resultsmentioning
confidence: 99%
“…Many papers reported on the design and development of platinum thin film RTDs and among them few researchers have analyzed the thermal hysteresis effects [5][6][7][8], thermal strain effects [9], thin film thickness effects [2], stagnation temperature [10], degradation effects at high temperature [11] and the long term stability [6,12] of the platinum RTDs. However temperature coefficient of resistance (TCR) plays an important role in determining the sensitivity of the RTD elementas it characterizes the average temperature chance of a 1Ω RTD.…”
Section: Introductionmentioning
confidence: 99%
“…The polynomial correction function derived on the basis of this data reduces the remaining deviation to below ±0.05 K. For two following testing cycles in the calibrator the polynomial correction function from the first calibration cycle is applied. The sensors show deviations to the calibrator reference within ±0.05 K as illustrated in Figure 4 for one sensor (according to the observations of [12] and [13]). Prior to a last (4th) testing cycle in the calibrator, the 400 mm long sensor sheath was bent by 90° at its centre with a bending radius of 30 mm.…”
Section: Pt100 Calibration and Preliminary Studymentioning
confidence: 97%
“…Uncertainties in between ±1 K (1σ) are expected for a class A PT100 as defined by the IEC 60751 at absolute temperatures around 400°C. Gam et al [12] and Zvizdić et al [13] investigate the thermal hysteresis effects in industrial platinum resistance temperature detectors. Both groups observed a hysteresis around 0.1 K for absolute temperatures of 400°C.…”
Section: Pt100 Calibration and Preliminary Studymentioning
confidence: 99%
“…On the other hand, wireless real-time temperature monitoring facilitates the inspection and protection of machines [ 13 , 14 , 15 ]. Experiments [ 16 , 17 ] have shown that the resistance temperature detector (RTD) is ideal for temperature sensing because of its linearity, accuracy, long-term stability, and wide-range of temperature measurement.…”
Section: Introductionmentioning
confidence: 99%